Studia ekonomiczno-matematyczne – analiza wybranych aspektów oferty edukacyjnej - Dniestrzański, Piotr (Economic and mathematical studies – analysis of selected aspects of educational offer, 2011)
On the market today there is a very wide range of educational courses and specializations associated with broadly understood applications of mathematics in economics. Apparently similar (or almost identical) proposals of studies may, however, prove to be fundamentally different. This remains unchanged because of the still valid teaching standards. The author conducts an analysis of offers provided by selected universities in the area of the economic and mathematical studies, primarily focusing on two aspects: how the universities function in relation to the existing legal restrictions, and the candidates’ problems with choosing an appropriate offer
Didactics of Mathematics, 2011, Nr 8 (12), s. 5-16
Keywords: mathematical studies; educational market; educational standards